Morphophysiological changes and secondary metabolites produced by bean plants subjected to water stress: an integrative review (Research, Society and Development, 2022)
Beans of the genera Phaseolus, Vigna, and metabolism cultures C3, in general, are sensitive to drought and will present a series of responses to escape or resist this stress. These responses induce morphological changes, which are associated with changes in plant physiology, which directly influence the parameters of photosynthesis, stomatal conductance; transpiration; and efficiency in water use. Therefore, this literature review aims to demonstrate information about the morphophysiological changes of common beans of the genera Phaseolus and Vigna submitted to water stress, as well as correlate abiotic stress with the production of secondary metabolites capable of protecting these plants when subjected to adverse environmental conditions. An integrative literature review of articles published in the last two decades in the 'Portal de Periódicos da CAPES' and the databases: 'Scielo,' 'Science Direct' and 'Web of Science' to update state of the art on this subject mainly differential responses that bean plants demonstrate in drought conditions, as well as the primary, secondary metabolites produced by these crops under conditions of abiotic stress by water deficiency. The studies evaluated in this research demonstrated that productivity parameters are the most affected by water scarcity, especially when a water deficit is imposed in the reproductive phases of flowering and fruiting. Beans produce secondary metabolites of tannins, flavonoids, and anthocyanins to avoid water scarcity and produce osmoprotective solutes such as proline and antioxidant enzymes.